ROLE OF BRAND ASSOCIATIONS AND BRAND AWARENESS TOWARDS FINANCIAL SERVICES IN INDONESIA - Rianti Putri, Fania; Hertina, Dede; Faizun Mohamad Yazid, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to measure the relationship between the brand associations and brand awareness towards the brand equity in the financial services with specific customer based at Indonesia. The surveys used hybrid method where it combined both online and offline. The reason for hybrid is because customer who come to the centre may not stipulated to a specific time. Some may come after office hours and some could be early morning or night. Data of customers received from the service operators with the permission from customer. Offline data collections were done at the location in random time for 7 days. From the combine 700 questionnaires distributed, 551 responses were usable. The response rate is 78.7%. Results indicates that brand associations positively influence the brand equity but not the brand awareness. The situations occur because financial services with a limited unique services having difficulty to attract customer in recognizing their brands. After all, financial services are governed by the ministry that may monitor their marketing orientations as it involves the benefits of people as a whole. Creative advertisements are not a norm in financial services as such customer awareness is still remain based on their basics functions and requirements.